The introduction of animal traction into inland valley regions. 1. Manual labour and animal traction in the cultivation of rice and maize: A comparison - Lawrence, P.R.; Dijkman, J.T.; Jansen, G.P. (1997)
Rice, a cash crop, was grown in the alluvial valley bottom (fadama) of an inland valley region of central Nigeria. The main staple crop, maize, was grown on the adjacent upland areas. Both oxen and manual labour were used for initial cultivation (ploughing and harrowing for rice and ridging for maize). Times spent were 94•3 and 315•2 h/ha respectively for rice and 28•2 and 65•5 h/ha for maize. Plots cultivated by animal traction (AT) produced more weeds and required more time for weeding than manually cultivated ones. Thus although animal traction saved time at the most critical time of year, it did not save time overall. Total time values were 1045 and 1064 h/ha for rice using animal traction and manual cultivation respectively. Corresponding values for maize were 654 and 484 h/ha. Type of cultivation had no significant effect (P > 0•05) on yields of crops (4•50 and 4•55 t/ha, AT/manual, for rice and 1•60 and 1•83 t/ha for maize). Not weeding the plots reduced rice yields to 2•78 and 2•83 t/ha for ox and manual cultivation respectively and to virtually zero for maize.